Designing mobile learning communication aid as an android app - Chee, K. N. (American Scientific Publishers, 2016)
With advent of mobile technology, mobile learning has become a promising pedagogy approach in education realm which allow pupils to learn without constraint of fixed time and location. Moreover, it is notable that communication plays a paramount role in education regardless whoever we are. Handicaps included deaf-dumb and even blind who have impediment in their daily communication in our society need to communicate to normal people as well. They face problem to communicate in the special education school either. However, this kind of welfare for these special group always and has been neglected by mobile application developer. In this paper, we develop and design an android application namely Mobile Learning Communication Aid (MOLECOMAID) based on social constructivism theory, to be integrated in mobile learning application and will then verified its usability, usefulness and effectiveness for m-learning in future research. To this extent, we described the architecture and all the functionalities. This proposed application accommodates special user to communicate with society without hindrance, which mediated by any android platform supported mobile device. Although the proposed application is in the context of education, this application is versatile enough to be adapted for education in general and also non-educational settings with a little modification on the design. Seems mobile learning will go beyond the world of education in the present and the future. It is contemplated that the design and development of the proposed application will serve as a reference for other researchers and developer regarding future developments in mobile learning application.